A systematic review of experiences of advanced practice nursing in general practice. Issue 1 (December 2017) - Jakimowicz, Michael; Williams, Danielle; Stankiewicz, Grazyna
Abstract Background Despite efforts to achieve conceptual clarity, advanced practice nursing continues to reside in a liminal space, unable to secure ongoing recognition as a viable means of healthcare delivery. This is particularly evident in general practice where advanced practice role development is more fluid and generally less supported by the hierarchical structures evident in the hospital system. This review synthesises published qualitative studies reporting experiences of advanced practice nursing in general practice. The panoramic view provided by patients, nurses and doctors within this novel context, offers a fresh perspective on why advanced practice nurses have struggled to gain acceptance within the healthcare milieu. Methods We conducted a systematic review of qualitative studies that explored the experiences of patients, nurses and doctors who had contact with advanced practice nurses working in general practice. Published work from 1990 to June 2016 was located using CINAHL and PubMed. The full text of relevant studies was retrieved after reading the title and abstract. Critical appraisal was undertaken and the findings of included studies were analysed using the constant comparative method. Emergent codes were collapsed into sub-themes and themes. Results Twenty articles reporting the experiences of 486 participants were included. We identified one major theme: legitimacy; and three sub-themes: (1) establishing and maintaining confidence in the advanced practice nurse, (2) strengthening and weakening boundaries between general practitioners and advanced practice nurses and (3) establishing and maintaining the value of advanced practice nursing. Conclusions We set out to describe experiences of advanced practice nursing in general practice. We discovered that general practitioners and patients continue to have concerns around responsibility, trust and accountability. Additionally, advanced practice nurses struggle to negotiate and clarify scopes of practice while general practitioners have trouble justifying the costs associated with advanced practice nursing roles. Therefore, much work remains to establish and maintain the legitimacy of advanced practice nursing in general practice.